Training injury incidence in an amateur women`s rugby union team in New Zealand over two consecutive seasons - King, D.; Hume, P. A.; Clark, T.; Foskett, A.; Barnes, M. J. (Journal of Science and Medicine in Sport, 2021)
Objectives: To describe the training injury incidence in amateur women`s rugby union in New Zealand over two consecutive seasons. Design: A prospective cohort observational study Methods: A total of 69 amateur women`s rugby 15s team playerswere observed. Training exposure and training injury incidence were calculated. Results: The 38 training injuries resulted in a total injury incidence of 11.4 (8.3-15.6) per 1,000 training-hours. There were 12 injuries that resulted in a time-loss injury incidence of 3.6 (95% CI: 2.0-6.3) per 1,000 training-hours. Forwards recorded more total (RR: 1.8 [95% CI: 0.9-3.5]; p = 0.0516) and time-loss (RR: 2.0 [95% CI: 0.6-6.6]; p = 0.2482) injuries than Backs. The tackle was the most common injury cause for total (3.0 [95% CI: 1.6-5.6] per 1,000 training-hours.) injuries, but collisions (1.5 [95% CI: 0.6-3.6] per 1,000 training-hours.) with the ground or another person were the most common cause for time-loss injuries.The training injuries occurred most often to the lower limb and during the latter part of training sessions. These injuries were mostly minor in nature resulting in minimal time-loss away from training. Discussion: The time-loss injury incidence (3.6 per 1,000 training-hours.) for the amateur women`s rugby 15s team players was higher than that reported for National (1.2 per 1,000 training-hours.) and Rugby World Cup for women (0.2 to 3.0 per 1,000 training-hours.) competitions. Conclusion: The training injury incidence in amateur women`s rugby union in New Zealand was higher than that reported for national and international rugby union injury incidences.